Aggregation pathway complexity in a simple perylene diimide - Hyung Jun Kim; Changhwan Lee; P. James Schuck; Laura J. Kaufman (Scientific Reports)
Abstract This study characterizes the influence of self-assembly conditions on the aggregation pathway and resulting photophysical properties of one-dimensional aggregates of the simple imide-substituted perylene diimide, N, N’-didodecyl-3,4,9,10-perylenedicarboximide (ddPDI). We show that ddPDI, which has symmetric alkyl chains at the imide positions, assembles into fibers with distinct morphology, emission spectra, and temperature-dependent behavior as a function of preparation conditions. In all conditions explored, aggregates are one-dimensional; however, assembly conditions can bias formation to either J-like or H-like aggregates. Specifically, a solvent phase interfacial (SPI) method yields two types of aggregates with distinct morphology and photophysical properties while a surface and solvent vapor assisted method (SSVA) generates more uniform aggregates with H-dominant behavior. A combined SPI and SSVA approach facilitates the simultaneous generation and in situ characterization of distinct ddPDI assemblies, some of which assemble via seeded growth. Microscopic and spectroscopic imaging unveil the heterogeneity among ddPDI aggregates, each with unique photophysical properties including H-dominant aggregates with a very high degree of molecular alignment and uniformity in intermolecular organization. Overall, this study highlights the pathway complexity in self-assembly of even the simplest PDI molecules, paving the way for utilization of simple PDI aggregates in applications that demand diverse photophysical behavior.